What Kind of Citizen is Philosophy for Children Educating? What Kind of Citizen Should it be Educating? - Michaud, Olivier (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2020)
Philosophy for Children (henceforth P4C) is a program and a pedagogy for teaching philosophy in k-12 school that was first developed by Matthew Lipman and Ann Margaret Sharp. The P4C approach is generally presented as a valuable form of education for democratic citizenship. This relationship is so obvious that it often remains underdeveloped: P4C is constructed with the goal of developing children to be critical thinkers and to know how to dialogue with others, which are also hallmarks of what is wanted in the citizens of our democracies. The objective of this article is to explore and deepen this connection by analyzing how it has been developed in the literature of the P4C movement. What emerges from this study is that there are differences of opinions as to why P4C is an appropriate kind of education for democracy. From the texts analyzed, three pedagogies stood out in that regard: Deweyan pedagogy, critical pedagogy, and pedagogy of interruption. I analyze the different visions of P4C as a democratic education in each of these, present the different criticisms they offer to P4C in that regard, and propose how P4C may answer these criticisms. I conclude with the importance of practitioners being aware of the different perspectives that encompass P4C concerning its role for education for democratic citizenship.